The effects of Massa Medicata Fermentata on the digestive function and intestinal flora of mice with functional dyspepsia - Wang, Shuyu; Li, Yuanlin; Yang, Xiaoqi; Hao, Yinxue; Zhan, Xueyan (Frontiers in Pharmacology, 2024)
The purpose of this study was to identify the chemical components of Massa Medicata Fermentata in different fermentation methods, analyze its regulatory effects on gastrointestinal propulsion and intestinal flora in mice with food accumulation, and further explore its mechanism of action in the treatment of dyspepsia. The chemical compositions of three MMFs were identified by UPLC-Q Extraction Orbitarp-mass spectrometer. The food accumulation model of mice was established. Gastric emptying rate and intestinal propulsion rate were calculated, serum gastrin concentration and cholinesterase activity were measured, and 16S rRNA microbial detection was performed in different groups of mouse feces. The results showed that a total of 95 chemical components were identified from the three MMF extracts, of which 62 were the same, but there were differences in flavonoids and their glycosides, organic acids and their esters. MMF, PFMMF and commercial MMF all could significantly improve the gastric emptying rate, intestinal propulsion rate and GAS concentration in the serum of model mice, PFMMF has a better effect, while there was no significant difference in cholinesterase activity among the groups (P >0.05). The 16S rRNA sequencing results showed that the MMF and PFMMF could increase the content of beneficial bacteria Bacteroidetes and decrease the pathogenic bacteria Verrucomicrobia in the intestines of model mice while the commercial MMF could not. Studies suggest that MMF has a variety of possible mechanisms in improving food accumulation, treating gastrointestinal dyspepsia, which provides reference value for quality evaluation and clinical application of MMF.